Voyages ... : Roman et récits ... - Regnard, Jean-François (Classiques Garnier, 2020)
Regnard n’a pas écrit que des comédies : sa captivité barbaresque et son voyage en Europe du Nord révèlent la richesse d’une écriture viatique complexe. Un roman et quatre récits de voyages traversant neuf régions, complétés par la relation de captivité de Fercourt, constituent cette édition. ... : Regnard wrote more than comedies: the narrative of his captivity among Barbary pirates and his journey to Northern Europe exemplify travel writing in all its richness and complexity. This edition includes a novel and four travel stories through nine regions, completed by Fercourt's report on their captivity. ...